THE THEORY OF THE RELATIONSHIP BETWEEN LANGUAGE AND CULTURE - Jo’raqulova Rayhon Xolboyevna (Web of Journals Publishing, 2025)
The relationship between language and culture has long been considered one of the most significant topics in the humanities. Language is not only a means of communication but also a powerful tool for preserving national identity, cultural values, and traditions. Through language, people express their worldview, collective memory, and social practices, while culture enriches the vocabulary, idioms, and symbolic meanings of the language. This mutual interaction shapes the mentality, social consciousness, and moral outlook of a nation. Culture evolves through language, and language, in turn, develops under the influence of cultural processes, historical experience, and social change. Therefore, studying them as an integrated system is crucial for understanding the dynamics of human society. This article analyzes the theoretical foundations of the interrelation between language and culture, highlighting their mutual enrichment and their impact on social development. The research also emphasizes the importance of linguistic and cultural studies in strengthening intercultural communication, preserving heritage, and fostering global understanding.
Keywords: Language, Culture, Linguoculturology, Society, Mentality, Tradition, Values, Thinking, Interaction, Social consciousness.